(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Business organizations are open systems that are directly affects and is affected by everything that happens around them in the business environment. One of the most important is the firms’ social responsibilityOne European Federation of Stock Exchanges report noted that part of the challenge of conducting research on family businesses is that there is currently no unified definition that defines a family business.The research aims to study the case of a family company to determine the extent of its commitment to implementing social responsibility, and then explain how to disclose this social responsibility in the financial statementsThe social responsibility of the Sindyan Family Company was evaluated through the activities it carries out, divided into the four axes of social responsibility (employees, environment, consumer, community) through a field visit to the company’s headquarters and conducting interviews with the company’s financial officer, workers and individuals in the company’s work environment, and some consumers for its products, and some beneficiaries of its social activities and subsidies provided to them. Results have been reached, the most important of which are:- Social responsibility as a concept differs from disclosing this responsibility, and Sindian Company undertakes many aspects of social responsibility without having a clear approach to disclosing them, and mixes what is social responsibility with what is charitable work, and what is paid is disclosed within the cost items that make the cost of its products higher. .- There is no special department at Sindyan Company responsible for social responsibility practices, and there is no organized annual plan within this area, but there is a perception among the owners of the company (the case studied) about the concept of social responsibility in an unorganized manner, and they are convinced of the importance of this responsibility.